Study of the state of the consumer basket of students (The Journal of Psychology and Sociology, 2019)
In search of possible solutions to contemporary problems of student youth, the current state of the state youth policy was analyzed and the need for active participation in solving existing problems was revealed. Studentship is the most active part of society, therefore the problems of social policy are directly related to young people, as evidenced by the international events of recent years. Any developed state should develop a social policy adequate to the social stratum of society.This problem was studied in works of such foreign and Russian scientists as E. Durkheim, R. Merton, T. Parsons, C. Polanyi, S. Ramon, P.M. Akhmadinurova, OS Vikhansky, N.A. Volgina, V.D. Kondratieva, A.I. Naumova, Z.P. Rumyantsev.The study was conducted in the context of improving the social security of the low-income part of the population, in particular students. The problem of the consumer basket of students is the most pressing social problem, due to the constant rise in the cost of food, and student scholarships are not indexed. According to our data, over 50% of students work to restore physical strength, not to mention the restoration of mental abilities. We have studied the food markets and prices for basic foodstuffs. The article presents an analysis of the study of the composition of the consumer basket of Kazakhstan students. The consumed foods of students are determined by a statistical method. We used the ranking method to determine the rank of each product in the students menu. Interpretation of the obtained research results is given.           Keywords: food, rank, ranking, minimum consumer basket, students, social standard